Habitat ecology of Pacific Black Brant and other geese moulting near Teshekpuk Lake, Alaska - Derksen, Dirk V; Eldridge, William D; Weller, Milton W (Wildfowl, 1982)
Behaviour, habitat selection, and foods of moulting Pacific Black Brant Branta bernicla nigricans and Canada Geese Branta canadensis were studied in 1977 and 1978, together with more general observations of White-fronted Geese Anser albifrons, at two large freshwater lakes near the Beaufort Sea in arctic Alaska. Moulting Brant and Canada Geese gathered in large flocks of up to 1,000 and 3,000, respectively, but flock size in White-fronted Geese was much smaller. Feeding flocks moved rapidly along shorelines and returned to the same sites every three to four days. All three species were highly social. Flocks responded to aircraft by moving from feeding or resting sites to the safety of open water or ice floes. Feeding dominated the 24-hour cycle and seemed most intense in morning and early evening hours. Brant and Canada Geese preferred moss zones immediately adjacent to open water compared to sedge zones more distant from the security of the lake. Deschampsia sp. and Carex sp. were the most important grass and sedge, respectively, found in Brant and Canada Geese droppings. Mosses were also found in droppings from both species at both sites, but percentages were considered abnormally high probably due to their tendency to fragment more readily than vascular plants. Grasses were higher in nitrogen and nonstructural carbohydrates than sedges. Percentage nitrogen, as well as phosphorous and potassium in above ground biomass declined from early July through early August and peaked as geese were in their second week of wing moult. Mosses had low values for all mineral and organic nutrients except calcium which was well above sedges and grasses. Vegetation cover and density were not significantly altered by flocks of grazing Brant and Canada Geese, but height and weight (biomass) of forage plants were significantly greater inside than outside exclosures. These data also demonstrated that moulting geese grazed the moss zone more intensively than the sedge zone. Protection of the Cape Halkett peninsula from petroleum development is recommended because of the unique combination of large isolated lakes that afford protection to moulting geese, and nutrient-rich food supplies that occur in abundant drained basins.